Selective X-ray induced NO-photodissociation in hemoglobin crystals: evidences from a crystallography-assisted Raman microscopy study - MERLINO, ANTONELLO; PICA, ANDREA; VERGARA, ALESSANDRO; M. R. Fuchs; A. Balsamo; F. Dworkowski; G. Pompidor; L. Mazzarella (2012)
X-ray induced radiation damage is a frequent phenomenon, especially when using third generation synchrotrons. Raman microscopy prior and after X-ray data collection can be a valuable tool to detect artifacts derived from radiation damage. Here we propose X-ray photolysis on crystals of NO-Hb as an additional experimental source of denitrosylation. The system under investigation is the Hb from an Antarctic fish, Trematomus bernacchii (HbTb). To the best of our knowledge, this is the first Raman-assisted crystallographic evidence of X-ray induced NO-photodissociation at a 3rd generation synchrotron (beamline X10SA of the Swiss Light Source).